A global event with a regional character: the Early Toarcian Oceanic Anoxic Event in the Pindos Ocean (northern Peloponnese, Greece) - Kafousia, N; Karakitsios, V; Jenkyns, H; Mattioli, E (Cambridge University Press, 2011)
The early Toarcian (Early Jurassic, ca 183 Ma) was characterized by an Oceanic Anoxic Event (T-OAE), primarily identified by the presence of globally distributed approximately coeval black organic-rich shales. This event corresponded with relatively high marine temperatures, mass extinction, and both positive and negative carbon-isotope excursions. Because most studies of the T-OAE have taken place in northern European and Tethyan palaeogeographic domains, there is considerable controversy as to the regional or global character of this event. Here, we present the first high-resolution integrated chemostratigraphic (carbonate, organic carbon, δ13Ccarb, δ13Corg) and biostratigraphic (calcareous nannofossil) records from the Kastelli Pelites cropping out in the Pindos Zone, western Greece. During the Mesozoic, the Pindos Zone was a deep-sea ocean-margin basin, which formed in mid-Triassic times along the northeast passive margin of Apulia. In two sections through the Kastelli Pelites, the chemostratigraphic and biostratigraphic (nannofossil) signatures of the most organic-rich facies are identified as correlative with the Lower Toarcian, tenuicostatum/polymorphum–falciferum/serpentinum/levisoni ammonite Zones, indicating that these sediments record the T-OAE. Both sections also display the characteristic negative carbon-isotope excursion in organic matter and carbonate. This occurrence reinforces the global significance of the Early Toarcian Oceanic Anoxic Event.